General Election Commission's Responsibility for Personal Data Leaks in the Election Database System - Armaini, Elza; Khalid, Khalid (IHSA Institute, 2024)
This research is a type of normative legal research with the aim of the research being to find out howstate responsibility for leaks of public data in the election database system andwhat legal measures can be taken againstpublic data leaks in the election database system. The results of this study indicate that the KPU must be responsible for cases of leaks of public personal data, this is based on Article 47 of Law No. 27 of 2022 concerning personal data protection which states that managers of public personal data are responsible for errors or negligence that cause leaks of per-sonal data. In addition, this legal responsibility is also strengthened by the legal substance in Article 12 of the Law which states that the public is given the right to sue and receive compensation for violations of the management of personal data. Furthermore, based on the civil law aspect, the public also has the right to legal remedies in the form of lawsuits through legitimacy and non-legitimacy, this is based on the provisions of Article 1366 of the Civil Code which states that everyone has the right to be responsible not only for losses caused by their actions but also for losses arising from their negligence. So from this article it can be concluded that the case of personal data leaks is a violation of negligence committed by the KPU which gives rise to legal responsibility that must be resolved by the KPU